In situ synthesis of high strength Ag brazing filler metals during induction brazing process. (1st January 2016) - Long, W.M.; Zhang, G.X.; Zhang, Q.K.
Graphical abstract: Abstract: In this study, a high Zn content AgCuZn alloy with poor forming property is in-situ synthesized using AgCu/ZnCu/AgCu sandwich sheet during the induction brazing process. The results reveal that the AgCu and ZnCu alloys can fuse comprehensively after they melt and been held for a short time, forming a brazing seam with uniform composition and superior metallurgical bonding with the 316LN substrate. The strength of the obtained brazed joints is much higher than the joints brazed using common AgCuZn alloy.